The Corrosion Behavior of Sputter?deposited W?xTa Alloys in 0.5 M NaCl Solution - Bhattarai, Jagadeesh; Baral, Susil (Nepal Journal of Science and Technology, 2013)
The corrosion behavior of the sputter–deposited amorphous and nanocrystalline W–xTa (x = 8–77) alloys was studied in 0.5 M NaCl solution open to air at 25°C using corrosion tests and electrochemical measurements. Tungsten and tantalum metals act synergistically in enhancing the corrosion resistance of the sputter–deposited W–xTa alloys and hence additions of 23 at. % of tantalum or more to the sputter–deposited W–xTa alloys were found to be effective to achieve significantly high corrosion resistance properties of the alloys than those of alloy– constituting elements. In particular, the corrosion rate of the W–60Ta alloy showed the lowest corrosion rate (that is, 2.0×10-3). The open circuit potential of the alloys shifted noble (positive) direction with immersion time. Addition of tantalum metal in W–xTa alloys is effective for ennoblement of the open circuit corrosion potential of the tungsten metal in 0.5 M NaCl solution open to air at 25°C. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 103-108 DOI: http://dx.doi.org/10.3126/njst.v14i1.8929